The muse - Burton, Jessie, 1982- (Ecco, an imprint of HarperCollins Publishers, 2016)
Odelle Bastien, a Caribbean émigré living in London in 1967, discovers a painting rumored to be the work of Isaac Robles, a young artist of immense talent and vision whose mysterious death has confounded the art world for decades. As she tries to sort through the conflicting stories of its discovery, she does not know who to believe, including her art gallery colleague, Marjorie Quick. The mystery surrounding the painting includes Olive Schloss, the daughter of a Viennese art dealer and English heiress, who lived in a small coastal Spanish village in 1936, just as Spain was heading into civil war; two illegitimate children of the local landowner, who become part of the Schloss family's lives; and deceit, lust, greed, and betrayal. --